PEMBINAAN DAN PENGAWASAN PEMERINTAH DESA TERHADAP BADAN USAHA MILIK DESA (BUMDES) DI DESA KAMPUNG BARU KECAMATAN CONCONG KABUPATEN INDRAGIRI HILIR TAHUN 2015 - Amarta, Muhammad Reza Eka; Tinov, M. Y. Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research aims to describe the guidance and supervision of the Village Government on Village-Owned Enterprises (BUMDes) in Kampung Baru Village, Concong District, Indragiri Hilir Regency in 2015. In this case it will be seen how the Village Government conducts guidance and supervision of Village-Owned Enterprises (BUMDes) . To find out this, the task of the Village Government will be measured based on the supervision concept through three indicators, namely (1) Establishing work results standards in the implementation of BUMDes (2) Conducting assessments and evaluations in the implementation of BUMDes. The study was conducted with a qualitative method through a descriptive approach to further analyze the data obtained from research in Kampung Baru Village, Concong District, Indragiri Hilir Regency qualitatively. Data sources are obtained from library studies, observations or observations, and interviews with resource persons. Based on the results of the study, it can be seen from three indicators, namely in setting the standard of work results of the Village Government BUMDES drafting a Village regulation together with the BPD as a reference for the implementation of BUMDes but have not been able to find specific results standards. Kampung Baru Village conducts village meetings together with all village officials and communities to evaluate and accommodate community aspirations and submit reports on the implementation of BUMDes. Remedial actions taken by the Village Government in following up on the problems that arise in BUMDes are limited to accommodating the aspirations and complaints of the community without any concrete action to improve. Keywords: Supervision, Village Government, Guidance of BUMDes